(6x+1)+x=4x+19

Simple and best practice solution for (6x+1)+x=4x+19 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for (6x+1)+x=4x+19 equation:


Simplifying
(6x + 1) + x = 4x + 19

Reorder the terms:
(1 + 6x) + x = 4x + 19

Remove parenthesis around (1 + 6x)
1 + 6x + x = 4x + 19

Combine like terms: 6x + x = 7x
1 + 7x = 4x + 19

Reorder the terms:
1 + 7x = 19 + 4x

Solving
1 + 7x = 19 + 4x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-4x' to each side of the equation.
1 + 7x + -4x = 19 + 4x + -4x

Combine like terms: 7x + -4x = 3x
1 + 3x = 19 + 4x + -4x

Combine like terms: 4x + -4x = 0
1 + 3x = 19 + 0
1 + 3x = 19

Add '-1' to each side of the equation.
1 + -1 + 3x = 19 + -1

Combine like terms: 1 + -1 = 0
0 + 3x = 19 + -1
3x = 19 + -1

Combine like terms: 19 + -1 = 18
3x = 18

Divide each side by '3'.
x = 6

Simplifying
x = 6

See similar equations:

| 4x+9=-107-7x | | (2-a)(2-a)-4=0 | | x+.23=24.60 | | 3-2y=(3y-2)-5y | | 7q+11=102 | | 14=3d-15+2a-6 | | 13-7x=143-42x | | 8x-30=3x | | 12p=168 | | ln(x)+ln(x-9)=ln(22) | | -5x-9x=-84 | | .75t-4=5 | | 5.7+1.1n=2.62 | | -5(t-9)-(t+1)=9 | | 6x-11=10-51 | | 225-4x=41x+15 | | 11-10-x=175-38x | | 11-1-x=175-38x | | x^2+16x+53=0 | | x+2=30 | | 0.04x-78.64=1.6 | | 2x+30=5 | | 2(x+2)=30 | | 13-8x=128-43x | | (x^2)+6x+8=0 | | 4x^2-49y^2=0 | | 4x+38=13x+70 | | 4x+38=18x+70 | | (5/8)h=160 | | 32+x=120 | | 7x-5=7(x+9) | | 90+x=140 |

Equations solver categories